New records of Lamiaceae (subfamily Nepetoideae) from Central Africa with the description of five new species - Meerts, Pierre J.; Paton, Alan J. (African Biodiversity & Conservation, 2026)
Background: Subfamily Nepetoideae is the last subfamily of Lamiaceae not yet dealt with by the Flore d’Afrique centrale, and many specimens are still unidentified in the collections.Objectives: To prepare the treatment of subfamily Nepetoideae (Coleus excluded) by analysing herbarium specimens.Methods: Herbarium material from BR, BRLU, K and POZG was studied.Results: Five species and one variety new to science are described (Equilabium mabwense, Fuerstia upembensis, Ocimum gnidioides, O. hirsutissimum var. paradoxum, Orthosiphon collinus, Plectranthus villosicaulis). Four new synonyms are proposed. A lectotype is designated for Ocimum fimbriatum. Fifteen taxa are reported as new to the Democratic Republic of Congo, two to Rwanda and one to Burundi. New records of rare taxa are also included.Conclusion: Of the 26 taxa discussed in this note, 20 are found in Haut-Katanga, highlighting the region’s significant contribution to the diversity of Lamiaceae subfamily Nepetoideae in Central Africa.